Monitoring Patients With Eosinophilic Esophagitis in Routine Clinical Practice - International Expert Recommendations - Arnim, Ulrike von; Biedermann, Luc; Aceves, Seema S.; Bonis, Peter A.; Collins, Margaret H.; Dellon, Evan S.; Furuta, Glenn T.; Gonsalves, Nirmala; Gupta, Sandeep; Hirano, Ikuo; Lucendo, Alfredo J.; Miehlke, Stephan; et al. (Clinical Gastroenterology and Hepatology, 2023)
Background & Aims: There are no studies or recommendations on optimal monitoring strategies for patients with eosinophilic esophagitis (EoE). Our objective was to develop guidance on how to monitor patients with EoE in routine clinical practice, on the basis of available clinical evidence and expert opinion. Methods: A multidisciplinary, international group of EoE experts identified the following important 3 questions during several consensus meetings: why, by what means, and when to monitor patients with EoE. A steering committee was named, and 3 teams were formed to review literature and to formulate statements for each topic. In a Delphi survey, a level of agreement of ≥75% was defined as threshold value for acceptance. In a final conference, results were presented, critical points and comments on the statements were discussed, and statements were rephrased/rewritten if necessary. Results: Eighteen EoE experts (14 adult and pediatric gastroenterologists, 2 pathologists and 2 allergists) with a median of 21.7 years in clinical practice, mostly academic or university-based, completed the Delphi survey, which included 11 statements and a proposed algorithm for monitoring patients with EoE. Each statement attained ≥75% agreement. Participants discussed and debated mostly about the statement concerning surveillance intervals for EoE patients with stable disease. Conclusions: It was concluded that effective maintenance treatment probably reduces the development of EoE complications, and regular, structured, and, under certain conditions, individualized clinical follow-up is recommended to assess disease activity while opening a window to monitoring side effects, adjusting therapy, and encouraging adherence to treatment. Follow-up should comprise symptom assessment and periodic or repeated endoscopy with histological assessment in specific EoE settings.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Delphi; Disease Monitoring; Eosinophilic Esophagitis; Surveillance